1. ## trying to understand why the answer is 6

I am trying to understand a math problem. I realize it is pretty basic; but, here it is: x - (-6) = 12

x - (-6) = 12
x - (-6) + (-6) = 12 -6
x = 6

I, however, came up with a different answer and I can't figure out why I am wrong. I am hoping someone here can help me. My answer is:

x - (-6) = 12
x - (-6) + (+6) = 12 + 6
x = 18
Any help would be appreciated

2. Originally Posted by seven
I am trying to understand a math problem. I realize it is pretty basic; but, here it is: x - (-6) = 12

x - (-6) = 12
x - (-6) + (-6) = 12 -6
x = 6

I, however, came up with a different answer and I can't figure out why I am wrong. I am hoping someone here can help me. My answer is:

x - (-6) = 12
remember negative*negative=positive
so, x + 6 = 12
x + 6 - 6 = 12- 6
x=6

Any help would be appreciated
.

3. thanks for the reply; but there is no multiplication, just subtraction in the problem

4. think of it this way.

x - (-6) = 12 if we let -6=a we have
x - a = 12 now what do we have to do to get x by itself? add a to both sides.
so we have x - a + a = 12 + a
x= 12 + a
x = 12 + (-6)
x=6

5. thanks...that, actually makes some sense to me